Optimal footwear longitudinal bending stiffness to improve running economy is speed dependent - Day, E.; Hahn, M. (Footwear Science, 2020)
The primary footwear components of interest to improve performance are midsole material, weight, and longitudinal bending stiffness. Little is known about the effects of varied longitudinal bending stiffness across a range of running speeds. The purpose of this study was to identify changes in spatiotemporal variables, horizontal ground reaction forces, subjective comfort, and metabolic cost at different running speeds in response to varied longitudinal bending stiffness. Ten highly trained males ran at 14, 17 and 20 km/h in shoes with varying longitudinal bending stiffness (normal 5.9, stiff 10.5 and very stiff 17.0 N-m/rad). Ground reaction forces, metabolics and subjective comfort assessments were collected. There were significant changes (p<.05) in contact time, stride frequency, and stride length between shoe conditions at all three speeds. Peak propulsive force decreased with increased bending stiffness at all three speeds, but there was no change in braking or propulsive impulse. The patterns of changes in stride length and stride frequency were different between speeds. At 14 km/h, most participants elicited a minimum metabolic rate in the normal shoe. However, at 17 km/h an increased number of participants were more economical in the stiff shoe, despite it weighing an extra 50 g compared to the normal shoe. Running speed had an influence on subjective comfort, with participants tending to prefer the normal shoe at 14 km/h and the stiff shoe at 17 km/h. These results suggest that an optimal bending stiffness to reduce metabolic cost and improve comfort may be running speed dependent.